Youth Entrepreneurship and its Potential in Dhaulagiri Region of Nepal - Adhikari, R. B. (AMC Indian Journal of Entrepreneurship, 2020)
This article was aimed at identifying the essence and potential of entrepreneurship. However, before this, the article conceptualizes the term entrepreneurship. For this, some literature related to entrepreneurship has been reviewed. Some assertive logic has also been used. It yielded some essential and facilitating factors of entrepreneurship. In the second part, the article describes the potential and problems of entrepreneurship in Dhaulagiri region of Nepal.